Variant antigen diversity in Trypanosoma vivax is not driven by recombination - Pereira, S.S.; Neto, K.J.G.A.C.; Duffy, C.W.; Richards, P.; Noyes, H.; Ogugo, Moses; André, M.R.; Bengaly, Z.; Kemp, Stephen J.; Teixeira, M.M.G.; Machado, R.Z.; Jackson, A.P. (Springer, 2020)
African trypanosomes (Trypanosoma) are vector-borne haemoparasites that survive in the vertebrate bloodstream through antigenic variation of their Variant Surface Glycoprotein (VSG). Recombination, or rather segmented gene conversion, is fundamental in Trypanosoma brucei for both VSG gene switching and for generating antigenic diversity during infections. Trypanosoma vivax is a related, livestock pathogen whose VSG lack structures that facilitate gene conversion in T. brucei and mechanisms underlying its antigenic diversity are poorly understood. Here we show that species-wide VSG repertoire is broadly conserved across diverse T. vivax clinical strains and has limited antigenic repertoire. We use variant antigen profiling, coalescent approaches and experimental infections to show that recombination plays little role in diversifying T. vivax VSG sequences. These results have immediate consequences for both the current mechanistic model of antigenic variation in African trypanosomes and species differences in virulence and transmission, requiring reconsideration of the wider epidemiology of animal African trypanosomiasis.